Handbook of Technical and Vocational Teacher Professional Development in the Digital Age - Han, Xibin; Zhou, Qian.; Li, Ming.; Wang, Yuping; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This is an open access book. Covering both theories and practices in Technical Vocational Education and Training (TVET) teacher development, this book provides up-to-date discussions and recommendations on issues relating to TVET teacher development in the digital age. It caters for the needs of in-service teachers and trainers, as well as TVET leaders who want to upscale their professional learning and development in terms of vision, knowledge, expertise, and industry skills needed in the transition to the digital era. What is particularly useful to TVET teachers/trainers are the proposed competency development framework, competency indicators, and the assessment instrument. Drawing on extensive research regarding TVET teachers$1 (Bcompetency development and today$1 (Bs industry needs, the proposed framework and indicators can be readily used to inform the self-assessment of one$1 (Bs professional competency level, so as to plan one$1 (Bs career trajectory accordingly.Teachers and trainers may also find the exemplary cases of teachers$1 (Bprofessional development from various countries inspiring and motivating. The book also serves as a useful reference for TVET leaders, administrators and teacher trainers. The book's competency framework, indicators, and strategies are an adaptable reference for planning professional development policies, evaluation mechanisms, and programs for teachers.s
Chapter 1. Introduction -- Chapter 2 Definitions and a review of relevant theories, frameworks and approaches -- Chapter 3 Professional competencies in TVET: Framework, indicators and assessment instrument -- Chapter 4 Strategies for developing TVET teachers$1 (Bprofessional competencies -- Chapter 5 Exemplars of good practice.s
Keywords: Teachers -- Training of; Professional education; Vocational education; Educational technology; Teaching and Teacher Education; Professional and Vocational Education; Digital Education and Educational Technology